NEMATODA PADA TIKUS SUKU MURIDAE DAN POLA INFEKSINYA DITAMAN NASIONAL LORE LINDU, SULAWESI TENGAH - Purwaningsih, Endang; Dewi, Kartika (Research Center for Biology-Indonesian Institute of Sciences, 2007)
The study of the patterns of nematode infection on rodents in Lore Lindu, Central Sulawesi was carried out. A total of 52 rodents were examined. Of these rodents 37 (71.15 per cent) were found to harbour nematode parasites and 15 (28.85 per cent) were free.There were found 10 species of nematode: Subulura andersoni, Syphacia muris, Heterakis spumosa, Cyclodontostomum purvisi,Hepatojarakus malayae, Molinacuaria indonesiensis, Protospirura muris,Rictularia tani, Trichuris muris dan Nippostrongylus muris that found in intestine, stomach, cecum and liver.The kind of infections were single (17.31 per cent) and association (53.84 per cent).The highest prevalence was 5. andersoni (44.23 per cent). Each of species nematodes had a specific habitat in their hosts. The greatest number of habitat that species of nematodes found was stomach (all of the species nematodes were found at the stomach).